Transmission Mode Predicts Specificity and Interaction Patterns in Coral-Symbiodinium Networks - Fabina, N.; Putnam, H.; Franklin, E.; Stat, Michael; Gates, R. (2012)
Most reef-building corals in the order Scleractinia depend on endosymbiotic algae in the genus Symbiodinium for energy and survival. Significant levels of taxonomic diversity in both partners result in numerous possible combinations of coral-Symbiodinium associations with unique functional characteristics. We created and analyzed the first coral-Symbiodinium networks utilizing a global dataset of interaction records from coral reefs in the tropical Indo-Pacific and Atlantic Oceans for 1991 to 2010. Our meta-analysis reveals that the majority of coral species and Symbiodinium types are specialists, but failed to detect any one-to-one obligate relationships. Symbiont specificity is correlated with a host's transmission mode, with horizontally transmitting corals being more likely to interact with generalist symbionts. Globally, Symbiodinium types tend to interact with only vertically or horizontally transmitting corals, and only a few generalist types are found with both. Our results demonstrate a strong correlation between symbiont specificity, symbiont transmission mode, and community partitioning. The structure and dynamics of these network interactions underlie the fundamental biological partnership that determines the condition and resilience of coral reef ecosystems. © 2012 Fabina et al.